Disclosing HIV status to sexual partner: Findings from a People Living with HIV Stigma Index 2.0 study in the country Georgia - Tamar Zurashvili; Mariam Pashalishvili; Valerie A. Earnshaw; Hyungrok Do; Natalia Zakareishvili; Jack DeHovitz; Suzan M. Walters; Mamuka Djibuti (PLoS ONE, 2025)
Background HIV status disclosure to sexual partner plays an important role in fostering transparency and reducing stigma, yet it remains a complex issue influenced by various sociodemographic, psychosocial, and experiential factors. This study investigated factors associated with HIV status disclosure to sexual partner among people living with HIV (PLHIV) in Georgia. Methods We conducted a secondary analysis of data from the PLHIV Stigma Index 2.0 study conducted in 2022–2023. Participants were recruited from HIV care centers and community-based organizations. Data collection utilized standardized questionnaires assessing sociodemographic factors, stigma, discrimination, and interactions with the healthcare system. Statistical analysis employed descriptive statistics, bivariate, and multivariate logistic regression to examine associations between stigma, sociodemographic factors, and status disclosure to sexual partner. Results Out of 765 participants, the mean age was 40.6 years, with a majority being male (67.4%). More than a fifth of respondents reported treatment interruptions, with 35.3% not disclosing their status to sexual partner. Disclosure was more common to close contacts than to others. Indicators of internalized stigma were common, with participants reporting feelings of guilt (40.1%), shame (36.1%), worthlessness (28.4%), and feeling ‘dirty’ (12.4%). Common behavioral reactions to stigma included avoiding medical visits (13.1%) and refraining from social support (10.5%). Over 40% did not disclose their status to sexual partner. Logistic regression highlighted that older age, knowing partner’s HIV status, positive disclosure experiences and enacted stigma were positively associated with status disclosure. Conclusion The complex dynamics between stigma and HIV status disclosure highlight the importance of providing decision support to PLHIV, helping them navigate disclosure process while considering potential risks and benefits. The findings emphasize the need for focused interventions that promote disclosure to sexual partner, especially among individuals with treatment interruptions, as it can significantly impact personal health and broader public health objectives, including the prevention of HIV transmission.